2006
DOI: 10.1021/ic060898e
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Modulation of Hyperpolarizable (Porphinato)zinc(II) Chromophores Featuring Ethynylphenyl-, Ethynylthiophenyl-, Ethynylthiazolyl-, and Ethynylbenzothiazolyl-Based Electron-Donating and -Accepting Moieties

Abstract: A series of conjugated (porphinato)zinc(II)-based chromophores structurally related to [5-(4-dimethylaminophenylethynyl)-15-(5-nitrothienyl-2-ethynyl)-10,20-bis(3,5-bis(3,3-dimethyl-1-butyloxy)phenyl)]zinc(II) were synthesized using metal-catalyzed cross-coupling reactions involving [5-bromo-15-triisopropylsilylethynyl-10,20-diarylporphinato]zinc(II), [5-bromo-15-(4-dimethylaminophenylethynyl)-10,20-diarylporphinato]zinc(II), [5-(4-dimethylaminophenylethynyl)-15-ethynyl-10,20-diarylporphinato]zinc(II), and [5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 73 publications
0
44
0
Order By: Relevance
“…12−14,17,18,25,26,29−36,55−62 Porphyrins and their corresponding ethynylated and ethyne-linked derivatives are attractive building blocks for such materials because of their extended electronic delocalization, large oscillator strengths, and substantial polarizabilities; 12−14,38,61,63−76 in addition to providing for substantial β λ values, such porphyrin-based donorbridge-acceptor systems manifest excellent thermal stabilities. 13,17,25,29,30,32,34,61 Benchmark examples of these robust structures that possess high β λ values include [5-((4′-(dimethylamino)phenyl)ethynyl)-15-((4″-nitrophenyl)-ethynyl)-10,20-diphenylporphinato]zinc(II) (D-PZn-A) 13,14,17 and closely related structures, 29,30,34 as well as chromophores where (porphinato)zinc(II) (PZn) and metal(II)polypyridyl (M) units are linked via an ethyne bridge (M-PZn species). 25,26,[29][30][31][32][33]36,57 The hyperpolarizabilities of these systems display complex irradiation wavelength dependences; measured values of β λ for these structures are as high as several thousand ×10 −30 esu.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…12−14,17,18,25,26,29−36,55−62 Porphyrins and their corresponding ethynylated and ethyne-linked derivatives are attractive building blocks for such materials because of their extended electronic delocalization, large oscillator strengths, and substantial polarizabilities; 12−14,38,61,63−76 in addition to providing for substantial β λ values, such porphyrin-based donorbridge-acceptor systems manifest excellent thermal stabilities. 13,17,25,29,30,32,34,61 Benchmark examples of these robust structures that possess high β λ values include [5-((4′-(dimethylamino)phenyl)ethynyl)-15-((4″-nitrophenyl)-ethynyl)-10,20-diphenylporphinato]zinc(II) (D-PZn-A) 13,14,17 and closely related structures, 29,30,34 as well as chromophores where (porphinato)zinc(II) (PZn) and metal(II)polypyridyl (M) units are linked via an ethyne bridge (M-PZn species). 25,26,[29][30][31][32][33]36,57 The hyperpolarizabilities of these systems display complex irradiation wavelength dependences; measured values of β λ for these structures are as high as several thousand ×10 −30 esu.…”
Section: ■ Introductionmentioning
confidence: 99%
“…13,17,25,29,30,32,34,61 Benchmark examples of these robust structures that possess high β λ values include [5-((4′-(dimethylamino)phenyl)ethynyl)-15-((4″-nitrophenyl)-ethynyl)-10,20-diphenylporphinato]zinc(II) (D-PZn-A) 13,14,17 and closely related structures, 29,30,34 as well as chromophores where (porphinato)zinc(II) (PZn) and metal(II)polypyridyl (M) units are linked via an ethyne bridge (M-PZn species). 25,26,[29][30][31][32][33]36,57 The hyperpolarizabilities of these systems display complex irradiation wavelength dependences; measured values of β λ for these structures are as high as several thousand ×10 −30 esu. 13,14,17,25,29,30,32,33,36 In this paper, we examine theoretically porphyrin-based NLO chromophores based on established D-PZn-A and Ru-PZn (ruthenium(II)[5-(4′-ethynyl-(2,2′;6′,2″-terpyridinyl))-10,20-bis(2′,6′-bis(3,3-dimethyl-1-butyloxy)phenyl)porphinato]zinc-(II)-(2,2′;6′,2″-terpyridine) 2+ ) motifs incorporating bridges that introduce proquinoidal character into the D−A conjugation pathway.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also combined our expertise in molecular nonlinear optics of organic chromophores in the field of porphyrin dyes as molecular scaffold 8,9 with that in the field of N-alkyl pyridinium acceptors 10 to engineer a new amphiphilic porphyrin dye 1 which exhibits a strong SHG signal in lipid membranes. Previous work has shown that related donoracceptor meso-ethynyl porphyrins exhibit strong second-order NLO activity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that related donoracceptor meso-ethynyl porphyrins exhibit strong second-order NLO activity. 8,9 We have modified the structure of these dyes by using polar pyridinium electron-acceptors, 10 and by omitting the orthogonal meso-aryl substituents, to create a molecule with high affinity for biological membranes. Our SHG dye can be viewed as a hybrid between donor-acceptor porphyrins and commercially available membrane-binding dyes, which can be used to probe potential changes via SHG despite their weak NLO activity.…”
Section: Introductionmentioning
confidence: 99%